Continuity of post-stroke care from hospital to home - Tegrado, Lindsay Allen R.; Saavedra, Apryll Raedine B.; Sereneo, Kate Anjelyn; Soriano, Thea Angelica P.; Torres, Paola Anne P.; Tureda, Revi C.; Velina, Athena Zea Marie M. (Manila College of Nursing University of the Philippines Manila, 2017)
Background of the Study

This study aims to determine if there are unmet needs of post-stroke patients during the
transition phase from hospital to home as perceived by their family caregivers. The specific
objectives are as follows: (1) determine the pre- and post-discharge care needs of post-stroke
patients as perceived by the patient’s family; (2) determine the practices of healthcare providers (HCPs) in preparing post-stroke patients pre- and post-discharge; and (3) determine if the self-reported practices of healthcare providers are congruent with the perceived pre-discharge and post-discharge care needs of post-stroke patients.



Methods

A descriptive research design was used in the study wherein two 18-item self-administered —
one for the family caregivers and one for the HCPs — based on the Stroke Questionnaire from
Picker Institute Europe were given. The sample of family caregivers and HCPs were selected
from tertiary hospitals in the City of Manila with the following inclusion criteria: for the family
caregivers: caring for a post-stroke patient, who is discharged 1 week to 18 months prior to
data collection, for an average of 8 hours per week, and is between 18 to 60 years old; whereas, for the HCPs, only having a work experience in any stroke unit was the criterion. There were no exclusion criteria. Utilizing GPower 3.1.9.2 using a moderate effect size of 0.3, alpha of 0.05 and power of 0.95, 111 was computed as the sample size. There were a total of 30 family caregivers and 56 HCPs who participated in the study. Descriptive statistics was obtained using Microsoft Excel. Ethical clearance was obtained from the University of the Philippines Manila Research Ethics Board (UPM REB) and the respective ethics board of the selected institutions.


Results

All of the listed pre-discharge and post-discharge care needs of the post-stroke patients
were met except for the need for information on side effects of medications (10%), information on volunteer and support groups (43%), information on stroke organizations or other important websites (63%), help from health and social services (30%) and help with speaking difficulties (17%). Most of the perceived met care needs were congruent with the self-reported addressed care needs of HCPs.

There were some care needs perceived by the family caregivers as not met, which were
also reported by the HCPs as not addressed. These needs were as follows: information on side effects of medications, information on volunteer and support groups, information on stroke organizations or other important websites, help and support with any emotional issue,
information on how to improve mobility, and help with speaking difficulties.

As a whole, the HCPs were able to provide for the care needs of post-stroke patients
except for the information on volunteer and support groups (54%), and information on stroke
organization (37%). The nurses and physicians generally met the perceived care needs of post-stroke patients while the therapists were able to provide just some of the care needs. Although every profession of the HCPs were not able to individually provide the health care needs completely, they were able to provide these care needs as a team.

Conclusion

This study showed that all of the care needs of post-stroke patients were perceived as met,
either fully or partially. The few needs which were not met were the same needs that were not
fully addressed by the healthcare providers. Hence, there is a congruence between the family
caregivers’ perceptions of the care needs and the report of the HCPs. The care needs that were not met were mostly informational needs on support groups and stroke organizations,
information on smoking cessation, and rehabilitative needs including assistance in speech
difficulties and mobility, and on emotional support. Although none of the HCPs per profession
were able to completely address every need, these care needs were generally met when services given to post stroke patients were taken as a whole.
Accomplishment report (In partial fulfillment of the requirements for the course N121.2: Intensive Nursing Experience) -- University of the Philippines Manila, June 2017.
Keywords: Intensive community experience